Gestión de calidad y competitividad en la empresa La Casa de las Enchiladas, Iquitos 2023 - Cardenas Saavedra, Joao José (2023)
The objective of this work was to determine how quality management relates to competitiveness in the company La Casa de las Enchiladas, Iquitos 2023. The study population consisted of 61 restaurant customers, a resulting Pearson correlation score of 0.723 was obtained. **. With a sigma of 0.000, therefore, the hypothesis is accepted, and it is confirmed that there is a significant relationship. The questionnaire was applied as an information collection instrument through the survey, obtaining as a result of Cronbach's Alpha 0.887 and 0.758 in the variable of quality management and competitiveness respectively.